Development of Indonesian literary history learning media based on Bengkulu ethnic literature assisted by the Thunkable Application - Hiasa, Fina; Amrizal, Amrizal; Supadi, Supadi; Yanti, Nafri (Universitas Ahmad Dahlan, 2025)
This study aims to develop learning media for the History of Indonesian Literature Based on Bengkulu Ethnic Literature Assisted by the Thunkable Application. Good learning media is not only innovative and interactive with digital technology embedded in it, but also contains meaning in its teaching materials. Through the development of learning media for the History of Indonesian Literature based on Bengkulu ethnic literature, it is expected to improve the quality of learning and students can understand their local wisdom so that their love for the nation's culture increases. This study uses the Research and Development (R&D) method, where the research sample is students taking the History of Literature course, FKIP Unib. The research instrument used to collect data in this study uses a questionnaire and test techniques. There are three questionnaires that will be distributed in this study, namely a material expert questionnaire, a media expert validation questionnaire, and a student response questionnaire. The test technique is in the form of an evaluation that aims to determine the extent of students' understanding of the material after the learning media for the history of Indonesian literature based on Bengkulu ethnic literature assisted by the thunkable application is tested. The research produced a product in the form of Indonesian Literary History learning media based on Bengkulu Ethnic Literature by utilizing the help of the thunkable application. The researcher presents 10 original Bengkulu folk tales as part of the Literary History material. Students' knowledge of Bengkulu society's culture has increased and students' interest in learning has increased. This android-based learning media was validated by media experts, material experts, and also media users with a total overall result of 3.95, which in other words this media is suitable for use in learning activities. The combination of Indonesian literary history with Bengkulu ethnic literature received a good response from users.